Monoclonal antibody targeting mu-opioid receptor attenuates morphine tolerance via enhancing morphine-induced receptor endocytosis - Jia-Jia Zhang; Chang-Geng Song; Miao Wang; Gai-Qin Zhang; Bin Wang; Xi Chen; Peng Lin; Yu-Meng Zhu; Zhi-Chuan Sun; Ya-Zhou Wang; Jian-Li Jiang; Ling Li; et al. (Journal of Pharmaceutical Analysis, 2023)
Morphine is a frequently used analgesic that activates the mu-opioid receptor (MOR), which has prominent side effects of tolerance. Although the inefficiency of morphine in inducing the endocytosis of MOR underlies the development of morphine tolerance, currently, there is no effective therapy to treat morphine tolerance. In the current study, we aimed to develop a monoclonal antibody (mAb) precisely targeting MOR and to determine its therapeutic efficacy on morphine tolerance and the underlying molecular mechanisms. We successfully prepared a mAb targeting MOR, named 3A5C7, by hybridoma technique using a strategy of deoxyribonucleic acid immunization combined with cell immunization, and identified it as an immunoglobulin G mAb with high specificity and affinity for MOR and binding ability to antigens with spatial conformation. Treatment of two cell lines, HEK293T and SH-SY5Y, with 3A5C7 enhanced morphine-induced MOR endocytosis via a G protein-coupled receptor kinase 2 (GRK2)/β-arrestin2-dependent mechanism, as demonstrated by immunofluorescence staining, flow cytometry, Western blotting, coimmunoprecipitation, and small interfering ribonucleic acid (siRNA)-based knockdown. This mAb also allowed MOR recycling from cytoplasm to plasma membrane and attenuated morphine-induced phosphorylation of MOR. We established an in vitro morphine tolerance model using differentiated SH-SY5Y cells induced by retinoic acid. Western blot, enzyme-linked immunosorbent assays, and siRNA-based knockdown revealed that 3A5C7 mAb diminished hyperactivation of adenylate cyclase, the in vitro biomarker of morphine tolerance, via the GRK2/β-arrestin2 pathway. Furthermore, in vivo hotplate test demonstrated that chronic intrathecal administration of 3A5C7 significantly alleviated morphine tolerance in mice, and withdrawal jumping test revealed that both chronic and acute 3A5C7 intrathecal administration attenuated morphine dependence. Finally, intrathecal electroporation of silencing short hairpin RNA illustrated that the in vivo anti-tolerance and anti-dependence efficacy of 3A5C7 was mediated by enhanced morphine-induced MOR endocytosis via GRK2/β-arrestin2 pathway. Collectively, our study provided a therapeutic mAb, 3A5C7, targeting MOR to treat morphine tolerance, mediated by enhancing morphine-induced MOR endocytosis. The mAb 3A5C7 demonstrates promising translational value to treat clinical morphine tolerance.